2012
DOI: 10.1302/0301-620x.94b3.27679
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation of Beta-hCG expression in patients with osteosarcoma

Abstract: There are eight reported cases in the literature of osteosarcomas secreting β-hCG. Our primary aim was to investigate the rate of β-hCG expression in osteosarcoma and attempt to understand the characteristics of osteosarcomas that secrete β-hCG. We reviewed 37 histopathology slides (14 biopsies and 23 surgical specimens) from 32 patients with osteosarcoma. The slides were retrospectively stained for β-hCG expression. Patient and tumour characteristics, including age, gender, tumour location, subtype, proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 7 publications
1
23
3
Order By: Relevance
“…However, multiple case reports demonstrate high serum P-hCG in osteosarcoma patients [9,10,12,13,24,25], so it may be of value to study a larger sample of osteosarcoma patients with clinically elevated P-hCG levels to confidently determine the relationship between serum P-hCG and clinical outcomes in osteosarcoma patients. Our findings differed from the conclusion of Masrouha and colleagues [11], which suggested that immunohistochemical expression of p-hCG in tumor cells was associated with suboptimal tumor response, metas tases, and/or recurrence. In that case series, the frequency of P-hCG-positive staining (5/32 patients) was less than encountered in our study (28/49 patients).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, multiple case reports demonstrate high serum P-hCG in osteosarcoma patients [9,10,12,13,24,25], so it may be of value to study a larger sample of osteosarcoma patients with clinically elevated P-hCG levels to confidently determine the relationship between serum P-hCG and clinical outcomes in osteosarcoma patients. Our findings differed from the conclusion of Masrouha and colleagues [11], which suggested that immunohistochemical expression of p-hCG in tumor cells was associated with suboptimal tumor response, metas tases, and/or recurrence. In that case series, the frequency of P-hCG-positive staining (5/32 patients) was less than encountered in our study (28/49 patients).…”
Section: Discussioncontrasting
confidence: 99%
“…They reported weak versus strong staining intensity, which may be subjective. Our study used a different antibody against [3-hCG (polyclonal rabbit) than Masrouha and colleagues [11] (monoclonal mouse), and these antibodies may have different perfor mance characteristics, like sensitivity, specificity, and staining intensity. We chose to use a semi-quantitative system and defined 1% of staining as positive.…”
Section: Discussionmentioning
confidence: 99%
“…16 It is enticing to speculate that the undifferentiated nature of her tumor is a potential explanation for elaboration of b-hCG, although prior studies have not supported this association. 13,14 Although prior reports have suggested that b-hCG secretion is a marker of more aggressive osteosarcoma that is less responsive to chemotherapy, 14 this was not the case in the patient reported here. Indeed, despite neoadjuvant therapy with a suboptimal chemotherapy regimen (when viewed in retrospect), her tumor exhibited >90% necrosis at the time of resection, albeit after 3 cycles of therapy instead of the usual 2 in standard osteosarcoma therapy.…”
Section: Discussioncontrasting
confidence: 55%
“…From the few reported cases pertaining specifically to βhCG-secreting osteosarcomas, there is conflicting evidence as to whether tumorous βhCG production is indeed associated with a worse prognosis. Some studies have concluded that βhCG-secreting tumours are associated with the development of metastases, a suboptimal response to chemotherapy and/or tumour recurrence 16. Others have failed to detect any statistically significant differences in the development of metastases or in other clinical prognostic parameters 17…”
Section: Discussionmentioning
confidence: 99%